(untitled) (Encuentros, 2023)
In this paper, we discuss the expectations and aspirations that young students of a university in southwestern Colombia have about work. The research was carried out in two phases, one in which quantitative data was collected through a survey and the other, in which qualitative data was collected through an interview. We find that young students dream of the best of two worlds: stability and flexibility, in their stories these are added, intertwined, and coexist. In the world of longing, tensions have already been resolved.